Interview with Paul Kresge, president of ASI, September 20, 1969 (1969)
[00:00:00] Interviewer introduces Paul Kresge, President of Associated Students, Incorporated [00:00:23] Kresge talks about planning that had to take place over summer in preparation for the school year [00:01:12] Kresge talks about issue of parking, campus issues, and increased awareness for social issues [00:02:01] Kresge talks about students learning about their future and learning how to be part of a community [00:03:11] Kresge talks about community service operations that have been done recently: cleaning up floods, toy drive for Vietnamese children, helping disadvantaged children, Mission Mall design, etc [00:04:22] Interviewer begins to end interview